The effect of housing volume of a converting loudspeaker on the output electric power of a loudspeaker-based acoustic energy harvester - Ikhsan Setiawan (Universitas Sebelas Maret, 2020)
Acoustic energy harvester is a device that converts sound or acoustic energy into electrical energy. Generally, the main components of this instrument are an acoustic transducer and an acoustic resonator. In this study, the transducer used was a 4-inch woofer loudspeaker, without acoustic resonator but equipped with a cylindrical housing with a fixed cross-sectional area and a length that can be varied from 6 cm until 25 cm by using a piston. Experimental results for various housing volumes showed a similar pattern of the dependence of the generated electric power on the incoming sound frequencies. In addition, it was found that (within the range of the volume variations) the output electric power increased significantly when the volume of the housing was increased. The highest root-mean-square (rms) electric power obtained was 1.72 mW resulting from sound with a sound pressure level (SPL) of 105 dB and a frequency of 84 Hz and by using a length of the housing cylinder of 25 cm (housing volume of 3243.7 cm3)